Energy Expenditure and Maintenance Requirements in Non-Pregnant First-Parity Sows - Ryan S. Samuel; Soenke Moehn; Ronald O. Ball (Animals)
Five sows, non-pregnant after the first parity (body weight: 174 ± 11 kg), were used to determine energy expenditure (EE) measured as heat production (HP). Sows were fed first 1.0, then 2.0, times the recommended maintenance energy requirement (MEm) for one week each. Sows received half their daily ration in 16 half-hourly meals, then the remaining half in a large meal followed by an overnight fast in respiration chambers. Sows fed 1.0 MEm consumed 473 kJ ME/kg0.75 (22.8 MJ/d) and lost weight (−198 g/d) because HP (24.0 MJ/d) was greater than intake. Sows fed 2.0 MEm consumed 925 kJ ME/kg0.75 (44.9 MJ/d) and gained 1292 g/d and HP was 32.3 MJ/d. The respiratory quotient (RQ) of sows fed 2.0 MEm was greater than one, indicating body fat deposition. The HP when sows were eating repeated small meals (33.6 MJ/d) or a single large meal (29.8 MJ/d) was greater (p < 0.05) than the HP in the following 2 h (25.2 MJ/d). Based upon the recalculation of MEm using the present data, 506 kJ ME/kg0.75 is proposed as the MEm for non-pregnant modern sows.